THE PROBLEMS OF ELECTROMAGNETIC COMPATIBILITY IN POWER SYSTEMS WITH A POWERFUL FREQUENCY CONVERTERS - Saenko, Yu. L.; Baranenko, T. K. (Science and Transport Progress, 2008)
A comparative analysis of spectral composition of the output voltage and input current of frequency converters is described in this paper. An issue of choice of means of normalization of voltage quality indices in electric networks with frequency converters is also considered.